1983
DOI: 10.1007/bf00963999
|View full text |Cite
|
Sign up to set email alerts
|

A neurochemical study of developmental impairment of the brain caused by the administration of cytosine arabinoside during the fetal or neonatal period of rats

Abstract: Injection of pregnant rats with cytosine arabinoside (ara-C) (280 mg/kg) on day 15 of gestation caused a significant rise (about two times the control value) in monoamine concentrations (norepinephrine, dopamine, and serotonin) accompanied by a decrease (about 60% of the control) in the brain weight and DNA content in the cerebrum of the offspring at 60 days of age. When neonatal rats were injected with ara-C (30 mg/kg/day) for four consecutive days from the fourth to seventh days after birth, a decrease of DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Adlard et al 1975;Percy 1975;Woodward et al 1975;Johnston and Coyle 1979;Matsutani et al 1983;Ohno 1984;Chen and Hillman 1986;Gray et al 1986;Ono et al 1992;Gillies and Price 1993;Freeman et al 1995;Ferguson et al 1994Ferguson et al , 1996. One important finding from these experiments is that the timing and dose of the drug injection are key factors in determining the type and extent of damage to the developing nervous system.…”
Section: Discussionmentioning
confidence: 89%
“…Adlard et al 1975;Percy 1975;Woodward et al 1975;Johnston and Coyle 1979;Matsutani et al 1983;Ohno 1984;Chen and Hillman 1986;Gray et al 1986;Ono et al 1992;Gillies and Price 1993;Freeman et al 1995;Ferguson et al 1994Ferguson et al , 1996. One important finding from these experiments is that the timing and dose of the drug injection are key factors in determining the type and extent of damage to the developing nervous system.…”
Section: Discussionmentioning
confidence: 89%
“…23,41 Numerous studies have been made to evaluate the biochemical and neurochemical changes of microcephalic mice and rats. 23,41 In fact these authors have found a reduction (15 ± 80%) in monoamine such as dopamine, noradrenaline and serotonine contents accompanied by a decrease in the brain weight and DNA content in selected brain regions in offspring at the age of 60 days, (about 60% of the controls), 28,42 at the age of 90 days (about 80% of the controls). 28 Elevated speci®c activities of lysosomal enzymes (deoxyribonuclease, b-galactosidase, b-glucuronidase) were also observed in such studies.…”
Section: Brain Ota Concentration and Changes In Aminoacids Contentsmentioning
confidence: 94%
“…28 Elevated speci®c activities of lysosomal enzymes (deoxyribonuclease, b-galactosidase, b-glucuronidase) were also observed in such studies. 28,42 The lake or decrease of monoamine neurotransmitters in some areas of brain could be detrimental to the normal brain physiology.…”
Section: Brain Ota Concentration and Changes In Aminoacids Contentsmentioning
confidence: 99%
“…Official statistics reported 80% of prevalence diagnoses patients on treatment survive to malignant tumors (7). Chemotherapy is a useful tool to attack cancer and mellow down the sufferings which it entails, and cytarabine is the most common chemotherapeutic agent used in children (8), although its use is accompanied by elevation of monoamine concentrations in the brain regions (9). Guidelines on sugar consumption by the World Health Organization (WHO) recommend non-sugar sweeteners such as stevia and splenda as healthy sugar replacement alternatives (10).…”
Section: Introductionmentioning
confidence: 99%